The Survival Advantage of Females at Premenopausal Age Is Race Dependent in Colorectal Cancer. (30th December 2020) - Sheng, Hui; Wei, Xiaoli; Chen, Qunxi; Huang, Kewei; Han, Runkun; Liu, Yijun; Liu, Wen; Mao, Minjie
Abstract : Background . A female prognostic advantage in younger individuals has been demonstrated in various cancers. Several large-scale analyses based on different racial backgrounds have reported inconsistent results in colorectal cancer. The aim of the present study was to evaluate the prognostic value of sex and age in patients with colorectal cancer of different ethnic groups. Methods . We identified 71, 812 eligible patients from the Surveillance, Epidemiology and End Results database. According to age at diagnosis, the patients were categorized into premenopausal age (≤45 yrs), menopausal age (46–54 yrs), and postmenopausal age (≥55 yrs) subgroups for further analysis. Results . Multivariate analysis identified the female survival advantage to be significant in the premenopausal age subgroup (P = 0.002, HR (95% CI): 0.73 (0.60–0.89)), diminished in the menopausal age subgroup (P = 0.09 ), and absent in the postmenopausal age subgroup (P = 0.96 ). Furthermore, the female survival advantage at premenopausal age was significant only in white patients (P = 0.001, HR (95% CI): 0.68 (0.54–0.87)) and not in either American Indian/Alaska Native or Asian or Pacific Islander patients. There was a trend of better survival of females in black patients (P = 0.07 ). Conclusions . Sex was a major prognostic factor in colorectal cancer patients, especially premenopausal women, and the difference was also associated with race.